2013
DOI: 10.1155/2013/235018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BNP and CRP in Predicting the Development of Atrial Fibrillation in Patients Undergoing Isolated Coronary Artery Bypass Surgery

Abstract: Objective. To evaluate the association of BNP and CRP with the development of postoperative atrial fibrillation following coronary artery bypass grafting surgery. Methods. The series consists of 125 patients (aged 65 ± 9 years), who underwent isolated CABG-surgery. BNP and CRP levels were measured pre- and 24 hours postoperatively and their correlation to the development of postoperative AF was analyzed. Results. Forty-four patients (35%) developed AF postoperatively. They were significantly older (68 ± 8 vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Heart failure and AF often coincide with causal pathways in both directions . This is at least partly supported by our results confirming the known relationship between NT‐proBNP and AF (OR, 1·53; 95% CI, 1·24–1·88; P < 0·0001) in fully adjusted models which also included ∆GGT and ∆total bilirubin. On balance, the link between the failing heart and the liver described above also seems evident with the disappearance of the association between AF and GGT after adjusting for ∆total bilirubin as both GGT and bilirubin are elevated in congestive hepatopathy .…”
Section: Discussionsupporting
confidence: 88%
“…Heart failure and AF often coincide with causal pathways in both directions . This is at least partly supported by our results confirming the known relationship between NT‐proBNP and AF (OR, 1·53; 95% CI, 1·24–1·88; P < 0·0001) in fully adjusted models which also included ∆GGT and ∆total bilirubin. On balance, the link between the failing heart and the liver described above also seems evident with the disappearance of the association between AF and GGT after adjusting for ∆total bilirubin as both GGT and bilirubin are elevated in congestive hepatopathy .…”
Section: Discussionsupporting
confidence: 88%
“…Studies by Gasparovic et al and Pilatis et al showed elevated B-type natriuretic peptide (BNP) levels to be predictive of AF in patients undergoing CABG. 28 , 29 The utility of biomarkers in the setting of AF post cardiac surgery requires further clarification prior to a recommendation on their use but preliminary studies certainly show promise for AF prediction and thromboembolic risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies, mainly retrospective, have been conducted to clarify the pathogenesis of postoperative AF as well as to identify predisposing factors. However, the exact etiologic pattern still remains unclear ( 22 ). The proposed contributory factors include inflammation triggered by cardiopulmonary bypass, beta-blocker withdrawal, hyperthyroidism, caffeine, right coronary artery stenosis, atrial ischemia, inadequate intraoperative cardiac protection, perioperative ischemic injury, postoperative pericarditis, autonomic imbalance, and fluid/electrolyte disturbances during the intra-and post operative periods ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact etiologic pattern still remains unclear ( 22 ). The proposed contributory factors include inflammation triggered by cardiopulmonary bypass, beta-blocker withdrawal, hyperthyroidism, caffeine, right coronary artery stenosis, atrial ischemia, inadequate intraoperative cardiac protection, perioperative ischemic injury, postoperative pericarditis, autonomic imbalance, and fluid/electrolyte disturbances during the intra-and post operative periods ( 22 , 23 ). It is assumed that one of the reasons of POAF may be the post-operative local and systemic inflammations ( 24 ).…”
Section: Introductionmentioning
confidence: 99%